Exploring Freudian Psychoanalysis of Escapism and Foucauldian Panopticism in Eugene O’Neill’s Long Day’s Journey into Night 1956 - BENLARBI ,Soumia; Ben redda, Djamel (Faculty of Letters and Foreign Languages Department of English, 2019)
This dissertation analyses one of Eugene O’Neill’s plays as a new subject to study the psychological background of the playwright himself and the characters of this play. O’Neill wrote the script of play in which he portrayed his personal life and his suffering with his family, and summarized it in one summer day (August, 1912) and called it Long Day’s Journey into Night. This research paper also analyzes theories of popular thinkers and influencers such as Sigmund Freud’s Psychoanalysis theory, and Michel Foucault’s Panopticism. Briefly it is an attempt to discover the Freudian psychoanalysis theory by analyzing the characters behaviors, and then a Foucauldian reading of the play, Long Day’s Journey into Night by exploring panopticism throughout the events of the play. Therefore, the aim of this study is to call attention to the American theater and shed the light on O’Neill’s Long Day’s Journey into Night’s psychological characteristics. The play could be holding interested aspects to be analyzed and studied as it is the case of any other literary work, such as novels and short stories; especially the modern American theater plays which reflected the real daily struggle of the ordinary people of the American society